Tango and the political economy of passion - Savigliano, Marta (Boulder : Westview Press, 1995)
"Innovative historical study of the dance and musical lyrics of Tang o. Interweaves tales of sexuality, gender, race, class, and national id entity to examine relations between machismo, colonialism, and commodif ication as manifested in expressive culture"--Handbook of Latin America n Studies, v. 57.
Includes bibliographical references (p. 259-278) and index.
Keywords: Tango (Dance) -- Social aspects; Tango (Dance) -- Social aspects -- Argentina; Sex in dance